Resolution XVI Congress of Infectious Children of Russia «TOPICAL ISSUES OF INFECTIOUS PATHOLOGY AND VACCINE PREVENTION» December 12-14, 2016, Moscow, Russia - artiсle Editorial (LLC "Diagnostics and Vaccines", 2018)
.